2017
DOI: 10.1525/cse.2017.000547
|View full text |Cite
|
Sign up to set email alerts
|

Research into Genetically Modified Organisms in New Zealand: An Examination of a Sociotechnical Controversy

Abstract: New Zealand is known around the world as a country that is clean, green and “100% Pure.” The existence of genetically modified organisms in New Zealand is generally viewed as inconsistent with this identity, and there is therefore considerable public controversy surrounding research that utilises genetic modification techniques. In this paper, I examine the variety of interacting factors that are serving to shape this controversy, the influence it is having on research practices, and the implications for futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A 2013 random postal survey of New Zealanders reported that 42.2% agreed that 'GM poses a significant risk to the health and safety of humans' and only 12.7% of respondents agreed that 'GM products are safe for human consumption' (Chikazhe, 2015). Opposition to GM crops in New Zealand became pronounced in the early 2000s and is speculated to be driven by regulatory lapses and perceived conflict with 'clean and green' environmental values (Edwards, 2017).…”
Section: Gm Foodmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2013 random postal survey of New Zealanders reported that 42.2% agreed that 'GM poses a significant risk to the health and safety of humans' and only 12.7% of respondents agreed that 'GM products are safe for human consumption' (Chikazhe, 2015). Opposition to GM crops in New Zealand became pronounced in the early 2000s and is speculated to be driven by regulatory lapses and perceived conflict with 'clean and green' environmental values (Edwards, 2017).…”
Section: Gm Foodmentioning
confidence: 99%
“…New Zealand legislation currently prohibits the release of live genetically modified organisms into the wider environment and the importation of fresh GM fruit, vegetables or meat (Ministry for the Environment, n.d.). Some commentators have warned that this position limits New Zealand's competitiveness in the global agricultural market (Edwards, 2017;Fritsche, Poovaiah, MacRae, & Thorlby, 2018). More broadly, proponents of GM crops argue that GM foods can be beneficial on a global level.…”
Section: Gm Foodmentioning
confidence: 99%